Creating transformative spaces for dialogue and action: reflecting on the experience of the Southern Africa Food Lab - Scott Drimie; Ralph Hamann; Annie P. Manderson; Norah Mlondobozi (Ecology and Society, 2018)
Addressing food insecurity in South Africa requires innovative responses that fundamentally reconsider its causes, particularly because challenges facing the food system cut across issues, sectors, and scales. We discuss our experience in the Southern Africa Food Lab, a transformative space for diverse stakeholders from across the food system to engage in dialogue, paying particular attention to the relationship between dialogue and action. We argue that dialogue gives rise to action not only because it generates new ideas but because it creates commitments and relationships for new action. A particularly important aspect of such dialogue is to proactively address power imbalances and to give voice to the marginalized in the system. Such efforts, when implemented vigorously, likely result in a new set of challenges, but such resistance is a signal that indeed we are having at least some success at addressing deep-seated, structural dimensions of systems transformation.